2020
DOI: 10.3389/fimmu.2020.01481
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric Burn Survivors Have Long-Term Immune Dysfunction With Diminished Vaccine Response

Abstract: Epidemiological studies have demonstrated that survivors of acute burn trauma are at long-term increased risk of developing a range of morbidities. The mechanisms underlying this increased risk remain unknown. This study aimed to determine whether burn injury leads to sustained immune dysfunction that may underpin long-term morbidity. Plasma and peripheral blood mononuclear cells were collected from 36 pediatric burn survivors >3 years after a non-severe burn injury (<10% total body surface area) and from age/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Consistent with this, it has been demonstrated that pediatric burn patients have increased levels of circulating memory Tregs that resemble these injury responsive CD44 high Tregs in mice. These burn victims also showed long-term lower vaccine responses than uninjured controls, supporting our findings that injury-responsive memory Tregs are highly immunosuppressive ( 47 ). Consistent with our findings in mice, trauma patients have increased circulating levels of Tregs that can more potently suppressive T cell proliferation and patients that develop infections or sepsis showed higher circulating levels of Tregs ( 9 , 48 ).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with this, it has been demonstrated that pediatric burn patients have increased levels of circulating memory Tregs that resemble these injury responsive CD44 high Tregs in mice. These burn victims also showed long-term lower vaccine responses than uninjured controls, supporting our findings that injury-responsive memory Tregs are highly immunosuppressive ( 47 ). Consistent with our findings in mice, trauma patients have increased circulating levels of Tregs that can more potently suppressive T cell proliferation and patients that develop infections or sepsis showed higher circulating levels of Tregs ( 9 , 48 ).…”
Section: Discussionsupporting
confidence: 87%
“…The expression of IDO is upregulated in response to signalling by inflammatory cytokines including interferons (IFN-α, -β, and -γ) and TNF-α 24 . Previously reported cytokine data from this cohort demonstrated elevated levels of IFN-γ and TNF-α 26 . However, in the current study, although quinolinic acid, IFN-γ and TNF-α serum levels were all higher in the burn patients, the correlation between quinolinic acid and these cytokines was weak.…”
Section: Discussionmentioning
confidence: 47%
“…Of the 36 samples collected, Fifteen female and 18 male burn survivors provided sufficient plasma samples for analysis with three samples not sufficient for further study (n = 33 for analysis). Previous analysis using this cohort showed a diminished immune response in the burn injury survivors in comparison to their healthy uninjured counterparts 26 .…”
Section: Methodsmentioning
confidence: 67%
“…A study of severely burned children found that cytokines Interleukin 10 (IL-10), Granulocyte-macrophage-colony stimulating factor (GM-CSF), Tumor necrosis factor alpha (TNF-α), IL-2 and IL-17 were significantly elevated up to 3-years post-injury [ 11 ], indicative of a suppressive immune phenotype. A more recent study in non-severe burn paediatric patients [<10% total body surface area (TBSA)] similarly showed sustained increases of TNF-α, IL-2, IL-7 and Interferon gamma (IFN-γ) >3 years post-injury [ 12 ], and analysis of peripheral blood mononuclear cells showed significant increases in myeloid dendritic cells, memory CD4 + T cells and memory T-regulatory cells, providing evidence of long-term alterations in immune cell populations in paediatric burn patients. While similar studies are lacking in adults, the observation that even non-severe burn injury is associated with significantly increased risk and severity of infectious diseases and respiratory infections (determined by both admission rates and length-of-stay in hospital) over a follow-up period of around 15 years post-burn injury [ 6 , 8 ], suggests that immune dysfunction is also likely occurring in the adult burn population.…”
Section: Introductionmentioning
confidence: 99%